2016
DOI: 10.1073/pnas.1607903113
|View full text |Cite
|
Sign up to set email alerts
|

Real-time 3D imaging of microstructure growth in battery cells using indirect MRI

Abstract: Lithium metal is a promising anode material for Li-ion batteries due to its high theoretical specific capacity and low potential. The growth of dendrites is a major barrier to the development of high capacity, rechargeable Li batteries with lithium metal anodes, and hence, significant efforts have been undertaken to develop new electrolytes and separator materials that can prevent this process or promote smooth deposits at the anode. Central to these goals, and to the task of understanding the conditions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 27 publications
(42 reference statements)
3
102
0
1
Order By: Relevance
“…The in-operando NMR data showed an almost linear growth and decrease of the Li microstructure signal integral I µL for the second half of charging and the corresponding first half of discharging, respectively, as expected for a constant current experiment 12,29,36 . With one electron at most one Li + ion can be reduced and deposited on the Li-metal electrode and vice versa 42 .…”
Section: Long-run In-operando Nmr Of the Lithium Microstructure Formamentioning
confidence: 99%
See 1 more Smart Citation
“…The in-operando NMR data showed an almost linear growth and decrease of the Li microstructure signal integral I µL for the second half of charging and the corresponding first half of discharging, respectively, as expected for a constant current experiment 12,29,36 . With one electron at most one Li + ion can be reduced and deposited on the Li-metal electrode and vice versa 42 .…”
Section: Long-run In-operando Nmr Of the Lithium Microstructure Formamentioning
confidence: 99%
“…Such vertically standing battery housings were used for slice selective probing of a LIB in the stray field of a permanent magnet 39,40 and in combination with an additional coil for pulsed field gradients 31,32,41 . Moreover, three-dimensional 1 H MRI was applied to investigate the Li microstructure growth indirectly 42 . Crucial for all types of cell containers are sealing systems, current collector design and the choice of chemically resistant materials.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance (MR) techniques have been developed to measure several different cell properties 413 . A fundamental limitation that is difficult to overcome under typical operating conditions is that conductors are not transparent to rf irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Often, the cell casing is made of conductive material, such as polymer-lined aluminum in pouch or laminate cells, but also the electrodes preclude the use of conventional MR for realistic or commercial-type cell geometries. Nonetheless, MR has provided important insights into electrolyte behavior, Li-dendrite growth, and other electrochemical effects by the use of custom-built cells, which allow convenient rf access 413 .…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed that the growth of dendrites is not unidirectional, and after the dendrite growth, the morphology of the already formed structure does not change further throughout the experiment. Meanwhile, radio frequency study was also used in this study to quantify the MRI data obtained from this experiment …”
Section: Magnetic Resonance Techniquesmentioning
confidence: 99%